Mengelola Glokalisasi: Menelusuri Dinamika, Transformasi, dan Tantangan Pangan di Sulawesi Selatan - Muhammad Anas; Faisal Akbar Zaenal; Lily Dianafitry Hasan (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This study explores South Sulawesi's glocalisation. This study is conducted in Makassar City, Pare-Pare City, and Bulukumba Regency due to their higher urban and tourism context mobilisation, port accessibility, and port potential. This study investigates using phenomenology. Document analyses, observations, in-depth interviews, and focus group discussions (FGD) contribute to carefully selecting culinary or tourism industry experts as informants. According to the research, globalisation and localisation have affected South Sulawesi dishes' appearance, aroma, flavour, and environment (sight and touch). Since these are commercial dishes, fundamental ingredients and market values are essential. Since "traditional terminology" is devalued, contemporary cuisine is also gaining popularity. Modernisation and globalisation have altered the community's ontological security. Globalisation, technology, and transportation have altered every aspect of celebrations, including food. Due to the absence of a commercial context (anticipated monetary rewards), the festival is the only location where traditional culinary offerings are more likely to persist than elsewhere.